2017
DOI: 10.1007/s40122-017-0073-6
|View full text |Cite
|
Sign up to set email alerts
|

Hopes for the Future of Pain Control

Abstract: Here we aim to present an accessible review of the pharmacological targets for pain management, and succinctly discuss the newest trends in pain therapy. A key task for current pain pharmacotherapy is the identification of receptors and channels orchestrating nociception. Notwithstanding peripheral alterations in the receptors and channels following pathophysiological events, the modulatory mechanisms in the central nervous system are also fundamental to the regulation of pain perception. Bridging preclinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 71 publications
(83 reference statements)
1
67
0
Order By: Relevance
“…In the monoarthritic rats, the DNIC were present ipsilaterally at the three time points assessed, namely at early (seven days), intermediate (28 days), and prolonged (42 days) time points. This corroborates other studies indicating that DNIC events are active in chronic pain states [20,23,[31][32][33]. DNIC were previously found in the carrageenan model of acute monoarthritis [31], in the CFA-induced monoarthritis model [20], and in the monoiodoacetate-induced osteoarthritis [19], a model of joint pain with a neuropathic component at the later stages [24,25,34].…”
Section: Discussionsupporting
confidence: 91%
“…In the monoarthritic rats, the DNIC were present ipsilaterally at the three time points assessed, namely at early (seven days), intermediate (28 days), and prolonged (42 days) time points. This corroborates other studies indicating that DNIC events are active in chronic pain states [20,23,[31][32][33]. DNIC were previously found in the carrageenan model of acute monoarthritis [31], in the CFA-induced monoarthritis model [20], and in the monoiodoacetate-induced osteoarthritis [19], a model of joint pain with a neuropathic component at the later stages [24,25,34].…”
Section: Discussionsupporting
confidence: 91%
“…Nociception is a complex condition controlled by diverse neuromodulators including the monoaminergic systems noradrenaline (NA), 5‐hydroxytryptamine 5‐HT), and dopamine (DA) have diverse modulatory roles in pain signaling. (Bannister & Dickenson, ; Bannister, Kucharczyk, & Dickenson, ; Cortes‐Altamirano et al, ). Therefore, the possibility of drugs that modify the monoaminergic system, such as clomipramine or risperidone, could enhance antinociception activity of NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…NGF is a key molecule for the sensitization of primary nociceptors associated with tissue inflammation and it is increased in inflamed tissue (8). Preclinical data have revealed that neutralization of endogenous NGF prevents inflammatory hyperalgesia (8).…”
mentioning
confidence: 99%